The Effect of Using Animation Videos in Islamic Education Learning on Student Learning Outcomes at SD Negeri 102102 Rambutan - Erna; Sari, Nilam; Saragih, Delima (Program Studi Pendidikan Profesi Guru Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2024)
This research aims to improve student learning outcomes in Islamic religious education learning by using animated videos. This research is classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this research were elementary school students. This research data was obtained using test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this research is descriptive statistics by comparing the results obtained with indicators of research success. The research results show that animated videos can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completeness in each cycle with details of pre-cycle 40.49%, first cycle 50.77% and in the second cycle it increased to 88.12%. Thus, the use of videos can be used as an alternative to improve student learning outcomes in Islamic religious education learning.